O DESEMPENHO ACÚSTICO E AS EMPRESAS DE PROJETO DE ARQUITETURA À LUZ DA NORMA DE DESEMPENHO - Morais, Gabriela Alves Tenório de; Lira, Virgínia Queiroz; Pereira, Amanda Peixoto; Nascimento, Elivelthon Carlos do; Lordsleem Júnior, Alberto Casado; Melhado, Silvio Burrattino (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The residential buildings' acoustic performance is a featured subject nowadays. In this context, the NBR 15575 standard is an important tool to adapt the buildings' acoustic performance to the users' needs. This paper aims to evaluate whether architecture project companies are meeting the main guidelines proposed by the Performance Standard NBR 155575 regarding acoustic performance. The developed research consists of a descriptive nature field research whose strategy is the case study. The methodology was composed of the following stages: literature review; survey elaboration and its later application to the architecture companies; and result compilation and analysis. Through the data compilation it was observed that 85% of the companies were aware of the Performance Standard. As for the acoustic performance, it was observed that, although the respondents stated that noise conditions should be considered when designing projects, none of them requires measuring the noise level at the place and in the surroundings or uses software to assess acoustic performance. The identification of the obstacles faced by the architects to adapt projects to the Performance Standard and the proof of the low attendance to the acoustic performance's requirements comprise the main work contributions.